2017
DOI: 10.1111/jcmm.13271
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid promotes development of gastroesophageal reflux disease and Barrett's oesophagus by modulating integrin‐αv trafficking

Abstract: The fundamental mechanisms underlying erosive oesophagitis and subsequent development of Barrett's oesophagus (BO) are poorly understood. Here, we investigated the contribution of specific components of the gastric refluxate on adhesion molecules involved in epithelial barrier maintenance. Cell line models of squamous epithelium (HET‐1A) and BO (QH) were used to examine the effects of bile acids on cell adhesion to extracellular matrix proteins (Collagen, laminin, vitronectin, fibronectin) and expression of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The increased intestinal level of DCA after a high-fat diet is associated with the onset of many intestinal diseases including colorec-tal cancer. [30][31][32] However, the mechanism still remains to be elucidated. In the present study, we investigated the effects of DCA on the intestinal mucosal barrier and its role in the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The increased intestinal level of DCA after a high-fat diet is associated with the onset of many intestinal diseases including colorec-tal cancer. [30][31][32] However, the mechanism still remains to be elucidated. In the present study, we investigated the effects of DCA on the intestinal mucosal barrier and its role in the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Its potential procarcinogenic and proinflammatory actions lead to its uniqueness among bile acids [ 27 , 28 , 29 ]. It has been reported that DCA promotes the development of Barrett’s esophagus and esophageal disease [ 15 , 30 , 31 ]. In addition, DCA has been reported to be strongly associated with the occurrence of HCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors might be related to an increased or decreased risk of Barrett's esophagus and colorectal neoplasms, including the bile acid level, gastrin level, genetic factors, and treatment with nonsteroidal anti‐inflammatory drugs and/or aspirin …”
Section: Discussionmentioning
confidence: 99%